Different Strategies for Obtaining Enantiopure Hemicryptophanes - Colomban, Cédric; Châtelet, Bastien; Martinez, Alexandre (Synthesis, 2019)
Hemicryptophanes have recently emerged as an attractive class of cages due to their interesting applications as supramolecular receptors and catalysts. Over the last decade, substantial advances have been made regarding the preparation of enantiopure versions of these synthetic receptors. Enantiopure hemicryptophanes are commonly obtained through the separation of diastereomers by chromatography, or by resolution of racemic mixtures using chiral HPLC. This short review summarizes the existing methods to access to these chiral organic architectures and discusses the benefits and drawbacks of each approach.1 Introduction2 Enantiopure Hemicryptophanes Obtained by Introducing Additional Chiral Units and Separation of Diastereomers2.1 Synthesis by Means of Intramolecular Macrocyclization Reactions2.2 [1+1] Coupling of the CTV and the Southern Part3 Enantiopure Hemicryptophanes Obtained by Means of Chiral HPLC Resolution of Enantiomers3.1 Resolution of Hemicryptophane Racemates3.2 Resolution of CTV-Based Precursor Racemates4 Conclusion
Keywords: hemicryptophanes; chiral recognition; resolution; cyclotriveratrylene; supramolecular chemistry